Pembelajaran Daring Pemicu Degradasi Moral Pendidikan Di Era Pandemi Covid 19 - Mohammad Alif Saifuddin; Elya Umi Hanik (Al Hikmah: Journal of Education, 2020)
This study discusses the decline in the quality of education and morale of students in the Covid 19 pandemic era, which requires all learning at school to be done online. Online learning is very influential on the character and morals of students because it is not carried out face-to-face and the teacher cannot directly instill moral values in the classroom as the teacher's job should be, namely teaching and educating. The character of students will change for good or bad in this sparkling era of the pandemic issue if the parents of students can play a role as teachers in learning from this home. This study uses the library reset method. This research is expected to help teachers in instilling moral values in students in this distance learning.Penelitian ini membahas megnenai penurunan mutu pendidikan dan moral peserta didik di era pandemi covid 19, yang mengharuskan semua pembelajaran disekolah dilakukan dengan daring/online. Pembelajaran daring sangat berpengaruh pada karakter dan moral peserta didik karena tidak dilaksanakan secara tatap muka dan guru juga tidak bisa menanamkan nilai-nilai moral yang ada didalam kelas secara langsung seperti halnya tugas guru semestinya yaitu mengajar dan mendidik. Karakter peserta didik akan berubah menjadi baik atau buruk di era gemerlap isu pandemi ini, jika orang tua peserta didik  bisa berperan menjadi guru didalam pembelajaran dari rumah ini. Penelitian ini menggunakan metode perpustakaan reset. Penelitian ini diharapkan dapat membantu guru dalam menanamkan nilai-nilai moral peserta didik dalam pembelajaran jarak jauh ini.